Epstein-Barr Virus miR-BARTs 7 and 9 modulate viral cycle, cell proliferation, and proteomic profiles in Burkitt lymphoma - Caetano, Brunno Felipe Ramos [UNESP]; Rocha, Viviana Loureiro [UNESP]; Rossini, Bruno Cesar [UNESP]; Dos Santos, Lucilene Delazari [UNESP]; Elgui De Oliveira, Deilson [UNESP] (Elsevier, 2024)
The Epstein-Barr Virus (EBV) encodes viral microRNAs (miRs) that have been implicated in the pathogenesis of nasopharyngeal and gastric carcinomas, yet their potential roles in lymphomas remain to be fully elucidated. This study evaluated the impact of CRISPR/Cas9-mediated knockdown of EBV miRs BART-7 and BART-9 in EBV-positive Burkitt lymphoma cells Akata. As anticipated, the Akata cells subjected to CRISPR/Cas9-mediated knockdown of either EBV BART-7 or BART-9 exhibited a significant reduction in the expression of these viral miRs compared to cells with wild-type (wt) EBV genomes. This outcome effectively validates the experimental model employed in this study. Knocking down either BART-7 or BART-9 resulted in a notable reduction in cell viability and proliferation rates, alongside an elevation in the expression of EBV lytic genes. Global proteomic analysis revealed that the knockdown of EBV BART-7 significantly decreased the expression of ubiquitin/proteasome proteins while concurrently increasing RNA binding proteins (RBPs). Conversely, BART-9 knockdown reduced proteins associated with oxidoreductase activity, particularly those involved in fatty acid metabolism. Our findings unveil previously undiscovered EBV miRs BARTs 7 and 9 roles in cellular pathways relevant to both viral biology and lymphomagenesis.